The Influence of Ethical Leadership on the Quality of External Audits: A Business Management Perspective - Mariyani, Dede (ADMAN: Journal of Contemporary Administration and Management, 2024)
Ethical leadership has become a crucial topic in modern business management, particularly in the context of external audits. In an era where financial scandals and unethical business practices frequently emerge, the role of ethical leadership becomes increasingly relevant. This study aims to examine the influence of ethical leadership on the quality of external audits. Using a literature review method with a qualitative approach, data collection began with a search for relevant literature on Google Scholar for the period 2006-2024. The results of the study indicate that ethical leadership plays a significant role in enhancing the quality of external audits. Ethical leadership promotes transparency, integrity, and auditor independence while fostering a positive organizational culture. Ethical leaders also invest in the professional development of auditors, minimize the risk of conflicts of interest, and encourage the use of innovative audit technologies and methods. Case studies from various companies show that the implementation of ethical leadership can prevent financial scandals, improve audit efficiency and effectiveness, and build a long-term positive reputation. Overall, ethical leadership is proven to be a key factor in ensuring high-quality external audits, which in turn increases public trust in a company's financial statements.